Perancangan Sistem Pengendalian Motor Induksi 3 Phasa Menggunakan Variable Speed Drive dan Smart Relay Pada Pompa Irigasi Taman: Perancangan Sistem Pengendalian Motor Induksi 3 Phasa Menggunakan Variable Speed Drive dan Smart Relay Pada Pompa Irigasi Taman - Ni Komang Devi Purnamasari; I Wayan Sukadana; I Wayan Suriana (Universitas Pendidikan Ganesha, 2025)
Conventional garden irrigation pump operation with the on/off method causes the three-phase induction motor to operate at nominal speed without adjusting the water pressure requirements, resulting in high electrical energy consumption, current surges at starting, and unstable water pressure. This study aims to design and implement a three-phase induction motor control system based on Variable Speed ​​Drive (VSD) and Smart Relay to maintain stable water pressure and improve energy efficiency. The system consists of an 11 kW three-phase induction motor, a centrifugal pump, a VSD, a Smart Relay, and a pressure transmitter as a feedback sensor. The Smart Relay regulates the VSD output frequency based on the pressure signal. Test results show the system is able to maintain stable water pressure. The total power is reduced from 38.22 kW with the conventional method to 9.45 kW with the VSD system, with an energy efficiency of 75.27%. In addition, the starting current is significantly reduced.